LONG-TERM AND TIDAL DEFORMATIONS RECORDED BY EXTENSOMETERS AND TILTMETERS (TIEN SHAN - ALA-ARCHA OBSERVATORY) - Timofeev V.Yu.; Yakovenko V.S.; Duchkov A.D.; Zapreeva E.A.; Ducarme B. (My University, 2001)
Measurements performed by means of tiltmeters and extensometers in special-purpose underground observatories are an important part of the research on the crustal kinematic parameters in the northern Tien Shan. Long runs of tilts and deformations observed at the Ala-Archa underground station (42.63° N, 74.50° E) have been analyzed. Results of tidal analysis are reported. Slow variations in tilts and deformations reveal seasonal changes and slope effects caused by seismic activity of the region. The annual average rate of meridional compression was 3-10 -7 for the period 1985-97 and 7 -10 -7 for 1989-97.
Keywords: TILTMETRY; EXTENSOMETRY; GEOPHYSICAL MONITORING; ALA-ARCHA OBSERVATORY; TIEN SHAN; KYRGYZSTAN